Increasing the flexibility and feasibility of concentrated solar power plants by the addition of a low temperature energy storage system - Antonio Rovira; Antonio Jesús Subires; Rubén Barbero; Rubén Abbas (Results in Engineering)
This paper aims at increasing the flexibility of concentrated solar power plants. For this, it analyses the introduction of a secondary thermal energy storage system into concentrating solar power plants. The objective of this secondary storage system is to modulate the energy dispatch while increasing the potential incomes of the plant. The system consists of two water tanks at different temperatures in series with the preheaters of the feedwater line. The system is charged and discharged thanks to the modulation of the steam flow coming from the turbine bleeds. Three configurations are proposed and compared. The study proves that the plants with the secondary water thermal energy storage system can boost the power rate during periods of high demand at the expense of reducing the power during periods of low demand. The economic analysis shows that the incremental cost of the system is low compared to the potential revenues of dispatching energy at high electricity prices, and it can be considered feasible in a wide range of economic scenarios.